UPAYA KEPALA SEKOLAH MENGATASI HAMBATAN DALAM MENINGKATKAN KINERJA GURU DI SMP - Jamilah Jamilah; Warman Warman; Azainil Azainil; Yudo Dwiyono (Jurnal Muara Pendidikan, 2024)
This study aims to determine efforts to overcome obstacles in improving teachers' performance at SMP Negeri 1 Samarinda. This research used a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing.  The results showed that the supporting and inhibiting factors in improving the performance of SMP Negeri 1 Samarinda teachers have succeeded in improving facilities and providing support to teachers for self-development, creating a conducive learning environment at school, and adequate facilities to provide optimal learning experiences for students. While the inhibiting factor is the Principal's importance of paying attention to facilities and support for self-development, teachers face obstacles in understanding the personality of teachers in depth. 2) Efforts to overcome obstacles in improving teacher performance are deliberations, technical guidance, MGMP, listening to suggestions from the school community, taking positive steps, and adequate facilities and infrastructure availability.